Exploring the psychology of suicidal ideation: A theory driven network analysis. (September 2019) - De Beurs, D.; Fried, E.I.; Wetherall, K.; Cleare, S.; O' Connor, D.B.; Ferguson, E.; O'Carroll, R.E.; O' Connor, R.C.
Abstract: Two leading theories within the field of suicide prevention are the interpersonal psychological theory of suicidal behaviour (IPT) and the integrated motivational-volitional (IMV) model. The IPT posits that suicidal thoughts emerge from high levels of perceived burdensomeness and thwarted belongingness. The IMV model is a multivariate framework that conceptualizes defeat and entrapment as key drivers of suicide ideation. We applied network analysis to cross-sectional data collected as part of the Scottish Wellbeing Study, in which a nationally representative sample of 3508 young adults (18–34 years) completed a battery of psychological measures. Network analysis can help us to understand how the different theoretical components interact and how they relate to suicide ideation. Within a network that included only the core factors from both models, internal entrapment and perceived burdensomeness were most strongly related to suicide ideation. The core constructs defeat, external entrapment and thwarted belonginess were mainly related to other factors than suicide ideation. Within the network of all available psychological factors, 12 of the 20 factors were uniquely related to suicide ideation, with perceived burdensomeness, internal entrapment, depressive symptoms and history of suicide ideation explaining the most variance. None of the factors was isolated, and we identified four larger clusters: mental wellbeing, interpersonal needs, personality, and suicide-related factors. Overall, the results suggest that relationships between suicide ideation and psychological risk factors are complex, with some factors contributing direct risk, and others having indirect impact. Highlights: 12 of the 20 psychological factors were uniquely related to suicide ideation. Perceived burdensomness and internal entrapment made equal contribution to suicide ideation. Defeat, external entrapment and thwarted belonginess were mainly related to other factors than suicide ideation. Networks highlight complexity between psychological factors and suicide ideation.